Wild animals. (New York, N.Y. : Snapshot, 1994)
Text and photographs introduce wild animals from tigers to monkeys.
"For children ages 4-8 years"--P. [4] of cover.
Keywords: Animals -- Miscellanea -- Juvenile literature; Animals -- Miscellanea; Questions and answers